Pengaruh Penggunaan Media Digital Berbasis Pop-Up Book Terhadap Pemahaman Konsep Siswa - Risna Wati; Nurhasanah, Aan; Hermawati, Eli (JISPE Journal of Islamic Primary Education, 2025)
This study was motivated by the low understanding of students' concepts of IPAS subjects. This study aims to determine the differences and improvement in students' concept understanding between experimental classes using digital media based on Pop-Up Book and control classes using human digestion board media. This research uses a quantitative approach. The method used in this research is Quasi Experimental Design with the type of research Nonequivalent control group. The instrument used in this research is a test in the form of esay. The subjects in this study were grade V students. Data analysis techniques in this study used normality test, homogeneity test, t test and n-gain calculation. The test results show that the hypothesis is accepted, with the obtained t_ (count) (6.98) greater than t_table (2.02) and the calculation of n-gain shows an increase with a moderate category. So it can be concluded that there is a difference in the understanding of the concept of experimental class students using digital media based on Pop-Up Book with control class using human digestion board media, and there is a difference in increasing the understanding of the concept of experimental class students using digital media based on Pop-Up Book with control class using human digestion board media.